2019
DOI: 10.1371/journal.pone.0219684
|View full text |Cite
|
Sign up to set email alerts
|

Childhood otitis media: Relationship with daycare attendance, harsh parenting, and maternal mental health

Abstract: Psychological stress has been linked to developmental problems and poor health in children, but it is unclear whether it is also related to otitis media (OM). As part of a long-term study surveying the characteristics of childcare and development in Taiwan, we analyzed the relationship between OM and sources of psychological stress in children, such as poor maternal mental health and harsh parental discipline. We analyzed the data of 1998 children from the “Kids in Taiwan: National Longitudinal Study of Child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
2
2
0
Order By: Relevance
“…In our analysis presenting at Tables 2 and 3 , living with older siblings, the history of maternal chronic OM, and daycare attendance increased the incidence of OM. Thus, our results were consistent with the findings of the previous studies 5 , 25 , 26 .…”
Section: Discussionsupporting
confidence: 94%
“…In our analysis presenting at Tables 2 and 3 , living with older siblings, the history of maternal chronic OM, and daycare attendance increased the incidence of OM. Thus, our results were consistent with the findings of the previous studies 5 , 25 , 26 .…”
Section: Discussionsupporting
confidence: 94%
“…Smoking was associated with AOM from S. pneumoniae and remains an important risk factor in pediatric pneumococcal disease. Our study corroborates previous findings that the presence of siblings in the household is common in children with AOM, as well as having siblings in daycare ( 37 40 ).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported elevated stress among parents of children with severe conditions, such as diabetes (Van Gampelaere et al 2020), epilepsy (Operto et al 2021), inflammatory bowel disease (Diederen et al 2018), rheumatoid arthritis (Cousino and Hazen 2013), and cancer (Rodriguez et al 2012); but also among parents of children with less severe conditions, such as allergies (Jung et al 2023), atopic dermatitis (Meltzer and Moore 2008), and chronic ear infections (Chen et al 2019). A meta-analysis of various child health conditions and their associations with global parenting stress showed clear differences in the strength of the correlations (Pinquart 2018).…”
Section: Parental Separation Risk Following a Child Health Condition ...mentioning
confidence: 99%